An Analysis about Albanian Politics and Constitutional Changes of 2008 - Zotaj, Elda (Mediterranean Journal of Social Sciences, 2013)
In some Eastern Europe ex-communist countries, the political transition is still an unfinished process. There are many reasonsand causes that have contributed to the unsuccessful set out and within the timeframes of this process. In this way oftransformation, institutional democratization and the establishment of independent institutions had result a real challenge forthese countries. In the context of the whole, Albania is a special case regarding the conflict of the political actors reflected thisin slowing the institutional processes of country democratization. The main purpose of this paper is to examine the impact ithas had the politics and political class in the direction of institutional democratization process and the creation of independentinstitutions. The main argument of this paper is that the political class of these 20 years of transition is not yet completely welldetached from the totalitarian party-state system legacy, which is reflected in the not yet realization of independent and solidinstitutions of the Albanian state.